2023
DOI: 10.26434/chemrxiv-2023-q24pc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidation of Thiols with IBX or DMP: One-pot Access to Thiosulfonates or 2-Iodobenzoates and Applications in Functional Group Transformations

Abstract: Thiosulfonates are accessed by oxidation of feed-stock thiols using either DMP in DCM or IBX in MeCN at rt (~30 degree C). The protocol gives access to a variety of thiosulfonates in good to excellent yields from both aromatic and aliphatic thiols. The reaction with DMP is found to be better than IBX in terms of reaction rate and conversion, whereas the oxidation with DMP requires lower equivalent than IBX. Benzyl thiols are however found to follow a different reaction pathway when treated with DMP; O-benzyl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…When the reaction of a thiol with IBX (1.0 equiv) in MeCN was conducted at rt, after 24 h, both disulfide 3d and thiosulfonate 2d were isolated in 18 and 75% yields, respectively (SI, entry 4, Table S2). Hence, with a longer reaction time of 24 h than the previously reported of 2 h, the in situ generated disulfides could be further oxidized to thiosulfonates (entries 8 vs 4). Therefore, IBX was employed in an excess amount to further facilitate oxidation and reduce the reaction time.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…When the reaction of a thiol with IBX (1.0 equiv) in MeCN was conducted at rt, after 24 h, both disulfide 3d and thiosulfonate 2d were isolated in 18 and 75% yields, respectively (SI, entry 4, Table S2). Hence, with a longer reaction time of 24 h than the previously reported of 2 h, the in situ generated disulfides could be further oxidized to thiosulfonates (entries 8 vs 4). Therefore, IBX was employed in an excess amount to further facilitate oxidation and reduce the reaction time.…”
mentioning
confidence: 99%
“…For instance, the reaction with 1.0 equiv of IBX producing thiosulfonate in 75% and disulfide in 18% indicated that IBA is participating in the oxidation (SI, Table S2, entry 4). In fact, the oxidation with PIFA also suggested that the disulfides can be obtained from thiols . Consolidating the above observations, a plausible reaction mechanism for the conversion of thiols to thiosulfonates with IBX through the intermediary disulfides is shown.…”
mentioning
confidence: 99%
See 3 more Smart Citations